Mutation Analysis of the RPGR Gene in a Chinese Cohort - Liu, Hong-Li; Gao, Feng-Guan; Wang, Dan-Dan; Hu, Fang-Yuan; Xu, Ping; Chang, Qing; Xu, Ge-Zhi; Wu, Ji-Hong (Frontiers in Genetics, 2022)
Purpose: To investigate the clinical and genetic characteristics of the retinitis pigmentosa GTPase regulatory factor gene (RPGR) in a Chinese cohort. Methods: A retrospective analysis was performed on 80 subjects with RPGR-retinal dystrophy (RPGR-RD) for detailed genetic and clinical characterization. The panel-based next-generation sequencing of 792 causative genes involved in common genetic eye diseases was conducted in all individuals, followed by clinical variant interpretation. Information including age, sex, geographic distribution, family history, consanguineous marriage, age at symptom onset, disease duration, best-corrected visual acuity (BCVA) and complete ophthalmologic examination results was collected. Results: This cohort (41 males and 39 females) included 26 families (26 probands and their available family members) and 13 sporadic cases. The average age of these participants was 36.35±17.68 years, and the majority of the families were from eastern China (28 families, 71.79%). The average duration of disease in the probands was 22.68±15.80 years. In addition, the average BCVA values of the right and left eyes in the probands were 0.96±0.77 and 1.00±0.77, respectively. A total of thirty-four RPGR variants were identified, including 6 reported variants and 28 novel variants. Among these variants, NM_001034853.1: c.2899_2902delGAAG and c.2744_2745ins24 were considered de novo variants. The majority of the RPGR variants were classified as likely pathogenic, accounting for 70.59% of the variants (24 variants). The most common nucleotide changes and amino acid changes identified in this study were deletions (16 variants, 45.06%) and frameshifts (17 variants, 50.00%), respectively. Genetic analysis revealed that these RPGR variants were distributed in 10 different subregions of RPGR, and 70.59% of the RPGR variants (24 variants) were located in exon 15. Four RPGR variants, NM_001034853.1: c.2405_2406delAG, c.1345C>T, c.2218G>T and c.2236_2237delGA, occurred at a very high frequency of 28.21% (11 families) among 39 unrelated families. Conclusion: This study expands the known mutational spectrum of RPGR, and we provide a new reference for the genetic diagnosis of RPGR variants.